Dangerousness or Diminished Capacity? Exploring the Association of Gender and Mental Illness with Violent Offense Sentence Length - Davidson, Megan L. (American journal of criminal justice, 2015)
The presence of mental illness within criminal sentencing can be conceptualized both as a mitigating factor based on the diminished capacity argument and as an aggravating factor stemming from the perceived dangerousness stigma associated with mental illness. The current study tests these hypotheses for violent offenses using data from the 2004 Survey of Inmates in State Correctional Facilities within a weighted negative binomial regression framework. Separate analyses were conducted for male and female offenders to isolate gender effects in relation to the sentence length of offenders with a mental illness. The findings reveal that the presence of a mental illness tended to increase violent conviction sentence length reported by male offenders and decrease sentence length reported by female offenders, suggesting mental illness in the context of a violent conviction may be interpreted as evidence of diminished capacity for females and future dangerousness for males.